1989
DOI: 10.1016/s0022-5347(17)39044-4
|View full text |Cite
|
Sign up to set email alerts
|

Histology of Tumor Residuals Following Chemotherapy in Patients with Advanced Nonseminomatous Testicular Cancer

Abstract: A total of 111 patients with advanced nonseminomatous testicular cancer underwent cisplatin-based combination chemotherapy, followed by surgical removal of residual masses in 101. Surgery included retroperitoneal lymph node dissection in 92 patients, thoracotomy in 19 and hepatic resection in 1 (11 patients underwent 2 operations). Complete necrosis and/or fibrosis was found in 52 operative specimens, mature teratoma in 37 and vital malignant tumor in 12. Of the 11 patients who underwent 2 operations 4 had com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 17 publications
4
33
0
3
Order By: Relevance
“…be more complicated than it would otherwise have been shortly after the completion of chemotherapy. Finally, As histology determines the need for resection, attempts have been made to predict the histology after leaving masses with residual cancer unresected is a serious risk; the presence of viable cancer cells in the chemotherapy [23][24][25]. Steyerberg et al [25] found that the predictors of necrosis were the absence of teratoma residual mass determines the decision to administer additional chemotherapy [14].…”
Section: Methodsmentioning
confidence: 99%
“…be more complicated than it would otherwise have been shortly after the completion of chemotherapy. Finally, As histology determines the need for resection, attempts have been made to predict the histology after leaving masses with residual cancer unresected is a serious risk; the presence of viable cancer cells in the chemotherapy [23][24][25]. Steyerberg et al [25] found that the predictors of necrosis were the absence of teratoma residual mass determines the decision to administer additional chemotherapy [14].…”
Section: Methodsmentioning
confidence: 99%
“…20,21 Because approximately 50% of all residual masses contain necrosis only, many patients do not benefit from postchemotherapy surgical resection. 4,[21][22][23] Although surgical morbidity and mortality rates have been reduced substantially during the past decade, the ability to identify these patients with necrotic residual lesions …”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] The targeted field is defined by the upper edge of thoracic vertebra 11 and the lower edge of lumbar vertebra 5. Ipsilateral to the primary tumor, the lateral margin should extend to the renal hilum and the contralateral margin includes the processus transversus of the lumbar vertebrae.…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%